Exploring The Impact Of Sharir Prakruti On Obesity: A Case Study Perspective (International Journal of Environmental Sciences, 2025)
Obesity is a global health issue characterized by abnormal or excessive fat accumulation that may impair health. In Ayurveda, Sharir Prakruti (body constitution) plays a pivotal role in determining an individual’s predisposition to various diseases, including obesity. This case study investigates the relationship between Sharir Prakruti and obesity, emphasizing the role of Kapha-dominant constitution in metabolic imbalance and fat accumulation.A detailed Prakruti assessment and clinical examination were conducted on a 35-year-old female patient presenting with a BMI of 32.5 kg/m² and symptoms of fatigue, lethargy, and weight gain over the past two years. The patient was classified as Kapha-dominant based on standard Ayurvedic prakruti assessment tools. Further analysis of her lifestyle, dietary patterns, and metabolic functions revealed patterns consistent with Kapha prakruti, including slow digestion, preference for cold and sweet foods, and a sedentary routine.This case highlights how Sharir Prakruti, especially Kapha dominance, may contribute to obesity through inherent sluggish metabolism (manda agni), excessive tissue formation (meda dhatu), and low motivation for physical activity. The Ayurvedic approach emphasizes personalized treatment protocols that align with the individual's Prakruti for long-term management and prevention.This study suggests that understanding an individual's Prakruti offers valuable insights into the etiology and management of obesity. It reinforces the need for integrative health approaches combining modern diagnostics with Ayurvedic constitutional analysis.